Glucose Tightly Controls Morphological and Functional Properties of Astrocytes - Lee, Chun-Yao; Dallérac, Glenn; Ezan, Pascal; Anderova, Miroslava; Rouach, Nathalie (Frontiers in Aging Neuroscience, 2016)
The main energy source powering the brain is glucose. Strong energy needs of our nervous system are fulfilled by conveying this essential metabolite through blood via an extensive vascular network. Glucose then reaches brain tissues by cell uptake, diffusion and metabolisation, processes primarily undertaken by astrocytes. Deprivation of glucose can however occur in various circumstances. In particular, ageing is associated with cognitive disturbances that are partly attributable to metabolic deficiency leading to brain glycopenia. Despite the crucial role of glucose and its metabolites in sustaining neuronal activity, little is known about its moment-to-moment contribution to astroglial physiology. We thus here investigated the early structural and functional alterations induced in astrocytes by a transient metabolic challenge consisting in glucose deprivation. Electrophysiological recordings of hippocampal astroglial cells of the stratum radiatum in situ revealed that shortage of glucose specifically increases astrocyte membrane capacitance, whilst it has no impact on other passive membrane properties. Consistent with this change, morphometric analysis unraveled a prompt increase in astrocyte volume upon glucose deprivation. Furthermore, characteristic functional properties of astrocytes are also affected by transient glucose deficiency. We indeed found that glucoprivation decreases their gap junction-mediated coupling, while it progressively and reversibly increases their intracellular calcium levels during the slow depression of synaptic transmission occurring simultaneously, as assessed by dual electrophysiological and calcium imaging recordings. Together, these data indicate that astrocytes rapidly respond to metabolic dysfunctions, and are therefore central to the neuroglial dialogue at play in brain adaptation to glycopenia.